Ứng dụng công nghệ Lora trong nông nghiệp thông minh trên nền tảng OpenCv – Python - Lê Văn Cầu, Lê Quang Thành (2025)
Ứng dụng công nghệ Lora trong nông nghiệp thông minh trên nền tảng OpenCv – Python